ANALISIS MAKNA “GARANGAN” PADA QS. FᾹṬIR AYAT 32 DALAM DISKURSUS TAFSIR LISAN LORA ISMAIL ASCHOLY - Dina Yasmin, Arini (STAI AL-ANWAR SARANG, 2025)
This study analyzes the meaning of the term “garangan” in Lora Ismail Al-Ascholy's oral exegesis discourse on Surah Fātir verse 32. In the oral exegesis delivered through social media, Lora Ismail interprets lafadz ẓālimun linafsihi as “garangan,” a term that has distinctive cultural connotations in the local community. This study aims to understand the relevance of using the term in the context of da'wah and how this approach reflects the contextualization of Qur'anic exegesis. Using descriptive qualitative methods and a netnography approach, this study examines Lora Ismail's lectures uploaded on his Instagram account. The results show that the use of the term “garangan” aims to bring religious messages closer to the audience through a more familiar linguistic approach. This term not only reflects cultural adaptation in the delivery of tafsir, but also provides motivation for worshipers to continue improving themselves without feeling alienated from the religious community. This research contributes to the development of oral exegesis studies and shows how culture-based da'wah can strengthen religious understanding in Indonesian Muslim societies.